Outcomes of Kidney Transplantation with a CMV Matching Allocation Schema. (4th October 2017) - Strasfeld, Lynne; Basuli, Debargha; Norman, Douglas; Langewisch, Eric; Olyaei, Ali; Lockridge, Joseph
Abstract: Background: Cytomegalovirus (CMV) infection continues to be a major cause of morbidity in kidney transplant recipients. The CMV donor-positive (D+)/recipient-negative (R−) serostatus pairing poses highest risk for CMV disease. Methods: In September 2012, we adopted a CMV matching allocation policy at the centers served by our organ procurement organization, the Pacific Northwest Transplant Bank. CMV serostatus was used as a criterion in determining deceased donor kidney allocation, whereby R− kidney transplant recipients were preferentially paired with a D− organ, and R+ recipients with an R+ organ. We performed a retrospective analysis of CMV-related outcomes for 400 consecutive kidney recipients, 196 prior to (January 1, 2010– August 31, 2012) and 204 following (September 1, 2012–December 3, 2014) implementation of the CMV matching allocation schema at our center. We also looked at waitlist time for patients transplanted during the same period. Results: The percentage of D+/R− transplants performed decreased from 17.3% to 2.5% ( P  < 0.001) after implementation of the CMV matching allocation strategy (Figure 1). CMV viremia decreased from 13.3% to 5.9% ( P  = 0.0118), and CMV syndrome or disease decreased from 9.2% to 2.9% ( P  = 0.00859) (Table 1). The percentage of patients treated for CMV infection overall decreased from 10.7% to 5.4% ( P  = 0.0498). Median days on the waitlist prior to transplantation increased from 793 (PRE) to 944 (POST) due to growing wait list size, but neither R− nor R+ patients appeared to be disadvantaged: wait times increased from 808.5 to 958 for the R− subset and from 777.5 to 933 for the R+ subset (Figure 2). Conclusion: CMV disease occurred infrequently in our cohort, in the context of 6 months of valganciclovir prophylaxis post-transplant and post-prophylaxis pre-emptive monitoring strategy for our D+/R− recipients. Following implementation of an allocation schema that took CMV serostatus into account, the rate of CMV infection and antiviral treatment decreased significantly. Disclosures: L. Strasfeld, Merck: Independent Contractor, Salary